Integrating Spirituality in Counselling and Psychotherapy: Theoretical and Clinical Perspectives - Daniels, Carla; Fitzpatrick, Marilyn (Canadian Journal of Counselling and Psychotherapy, 2013)
In recent decades, spirituality has become a prominent focus of psychological inquiry. As research begins to elucidate the role of spiritual beliefs and behaviours in mental health and the influences of spirituality in psychotherapy, developing therapist competency in this domain has increased in importance. This article will first situate spirituality as an interdependent facet of culture and then expand the tripartite model of multicultural competency—attitudes, knowledge, and skills—to consider the theoretical, empirical, and practical foundation that supports existing spiritual competencies and work with clients’ spirituality. The applicability of spirituality within mainstream theories is reviewed and highlighted with a clinical case.